2020
DOI: 10.1155/2020/3814513
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hematological Parameters in Malaria, among Adult Patients Attending the Bamenda Regional Hospital

Abstract: Malaria, which is responsible for a substantial amount of deaths in endemic countries, has been shown to have both direct and indirect effects on the hematological parameters. Notwithstanding, some hematological parameters among populations living in malaria endemic regions have not been described consistently, as a standard for measuring malaria burden. Based on the above fact, this study was designed to assess some hematological changes and their diagnostic values in malaria infected patients. A total of 160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
(63 reference statements)
3
9
0
Order By: Relevance
“…Haematological parameters as an investigating tool for cases of early malaria infection may help to detect early complications associated with serious malaria infections so as to help in the cure for the patients and prevent death that may result from such complications. The hematological parameters changes in malaria infected blood sample have been reported [12,13]. The study also revealed that the infected patients tend to have significantly lower platelet, PCV and high FSR, which is in agreement with the present study where platelet counts and PCV where significantly lower in infected than the non-infected subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Haematological parameters as an investigating tool for cases of early malaria infection may help to detect early complications associated with serious malaria infections so as to help in the cure for the patients and prevent death that may result from such complications. The hematological parameters changes in malaria infected blood sample have been reported [12,13]. The study also revealed that the infected patients tend to have significantly lower platelet, PCV and high FSR, which is in agreement with the present study where platelet counts and PCV where significantly lower in infected than the non-infected subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in addition to females constituting the majority of the study participants, they were also more infected. In line with findings from other studies, higher malaria prevalence among females can be associated with exposure patterns, influenced by socio-economic roles [ 32 , 33 ]. An earlier study suggested that poverty-related issues affected female adoption of malaria control methods [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…parameters 30,[37][38][39] as has been widely published. The mean temperature reading of the malaria patients was 38.78 ± 1.39°C with a significant reduction in erythrocytes, hemoglobin, hematocrit, platelet levels, mean platelet volume, and plateletcrit.…”
Section: Discussionmentioning
confidence: 99%